Lessons and Insights from the CCAFS Results-Based Management Trial. Summary from the CCAFS Flagship 4 RBM trial projects survey - Schuetz, Tonya; Schubert, Cecilia; Förch, Wiebke; Thornton, Philip K.; Cramer, Laura K. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
Along with several other CGIAR research programs, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) has in 2014 been piloting a new way of doing business revolving around the use of results-based management (RBM). Six trial projects were selected via a competitive call in 2013 for regional activities under Flagship 4, Policies and institutions for climate resilient food systems. The RBM process itself involves a shift away from a logframe to an impact pathway (IP) approach based on theories of change, emphasising the contribution of research towards development outcomes. In the theory of change (TOC) pathways are defined from research and its outputs and results towards outcomes, i.e. changes in practices in next-users of research outputs such as policy makers, development organisations, and farmers.